2017
DOI: 10.3349/ymj.2017.58.2.312
|View full text |Cite
|
Sign up to set email alerts
|

Association between Metformin Use and Risk of Lactic Acidosis or Elevated Lactate Concentration in Type 2 Diabetes

Abstract: PurposeMetformin can reduce diabetes-related complications and mortality. However, its use is limited because of potential lactic acidosis-associated adverse effects, particularly in renal impairment patients. We aimed to investigate the association of metformin use with lactic acidosis and hyperlactatemia in patients with type 2 diabetes.Materials and MethodsThis was a cross-sectional study from a tertiary university-affiliated medical center. A total of 1954 type 2 diabetes patients were recruited in 2007–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 28 publications
1
11
0
1
Order By: Relevance
“…Other studies have also shown that metformin concentrations remain in a therapeutic range in mildly to moderately renal impaired patients [40]. At the same time, growing evidence suggests that the underlying disease associated with the tissue hypoxia rather than metformin use is related to lactic acidosis in diabetes [41][42][43]. In the present research, no case of lactic acidosis was observed during hospitalization for both groups.…”
Section: Discussionsupporting
confidence: 60%
“…Other studies have also shown that metformin concentrations remain in a therapeutic range in mildly to moderately renal impaired patients [40]. At the same time, growing evidence suggests that the underlying disease associated with the tissue hypoxia rather than metformin use is related to lactic acidosis in diabetes [41][42][43]. In the present research, no case of lactic acidosis was observed during hospitalization for both groups.…”
Section: Discussionsupporting
confidence: 60%
“…Metformin can reduce diabetes-related morbidities by up to 32%, diabetes-related deaths by up to 42%, and all-cause mortality by up to 36%. 1 Metformin inhibits gluconeogenesis by reducing expression of genes encoding gluconeogenic enzymes. Metformin also increases both insulin sensitivity of peripheral tissues and glucose uptake while decreasing fatty acid oxidation.…”
Section: Discussionmentioning
confidence: 99%
“…Although metformin is also a biguanide, it does not affect anaerobic lactate production, and the incidence of lactic acidosis with metformin treatment is up to 20-fold lower than that for phenformin. 1,4 Metformin is cleared by the kidneys, and its potential for accumulation in patients having decreased renal function could precipitate lactate accumulation. On the other hand, several studies found no association between metformin use and lactic acidosis, although there are reports of increased metabolic acidosis primarily in patients who had at least one condition associated with decreased tissue perfusion (e.g., renal failure, liver disease, heart failure, myocardial infarct, infection, shock, seizure, or alcohol abuse).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the potential risk of fatal lactic acidosis, metformin has long been under-prescribed, especially for patients with heart failure (HF) [10]. This situation has changed considerably following recent epidemiological studies that showed the risk of lactic acidosis associated with metformin use was not greater than that of other antidiabetic medications, and that metformin use in patients with DM and HF did not necessarily increase the risk of lactic acidosis [11,12]. We also found that the use of metformin was not associated with an increased incidence of HF in a case-control study of patients with T2DM who were first diagnosed with HF between 2013 and 2015 (Supplementary Table 1; available online).…”
Section: Current Status Of Metformin Use In Patients With Type 2 Diabmentioning
confidence: 99%